STRATEGI PENGELOLAAN TERUMBU KARANG DI KEPULAUAN SERIBU - Nyoman Darma Adi; Ario Damar; Luky Adrianto; Dedi Soedharma; Akhmad Solihin (Graduate School Bogor Agricultural University (SPs IPB), 2017)
The aims of this research is to analyse the issues and prolems in coral reef management in order to established the strategy to achieve sustainable coral reef management. The study done during period of July to November 2015 in the Kepulauan Seribu district, DKI Jakarta. Reseach method was descriptive with case study. Data gathering using the triangulation method. Furthermore, data analysis using AWOT (Analythical Hierarchy Procedure and Strenght-Weakness-Opportunity-Threath) which is the combination of SWOT and Analytical Hierarchy Process (AHP) technique. The results showed that the problems of coral reef management was different in North and South area and therfore, the strategy applied in two different area is different. Moreover, the best strategy for North area was located in 1st. quadrant (strategi Strength-Opportunity where for South area the strategy located at 2nd quadrant (strategi Strength-Treath).Based on this results, the best program to be applied at South area is Community based solid waste management while for North area is implement the Co-Management.